Psychological adjustment of Muslim Chinese international students in Malaysia - Tuerxun, Sainula; Ismail, Nik Ahmad Hisham; Abdullah, Mohammad Ridhuan; Khalid, Syahida (International Journal of Education, Psychology and Counselling (IJEPC), 2020)
International students are growing in numbers in Malaysian college and university campuses since the commercialization of education at the tertiary level introduced in the 1990s. More significantly, there is an increase in the Muslim student population as more and more young Muslims come to Malaysia from different parts of the world. For example, there is a substantial increase in Muslim students from the People’s Republic of China (PRC) who see Malaysia as a peaceful and developing Muslim country. The aim of this qualitative study is to explore the thoughts and experiences of Muslim students from China studying at different Malaysian universities. Six Muslim students from RPC were interviewed in this study, and based on the data obtained from the interviews, the findings were categorized into several themes. Most Muslim-Chinese students found it difficult to adjust to the new environment, especially in terms of climate, food, and infrastructure. The students also found that language was a barrier in their interactions with the locals. At the individual level, the students suffered from loneliness and homesickness and also found that their financial situation posed a challenge. In the course of the study, several coping strategies were identified that the students had adopted in their pursuit of knowledge in Malaysia. On the other hand, they felt supported in their efforts to adjust to living in Malaysia by university management, faculty members, local students, and friends. Overall, the students concluded that Malaysia is a peaceful and beautiful country characterized by the kindness, tolerance, and helpfulness of her people. Finally, the students recommended that services and facilities should be improved for all international students in Malaysia